2004
DOI: 10.1038/sj.cr.7290215
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the activating signals in NK92 cells by recombinant GST-sHLA-G1α chain

Abstract: The soluble HLA-G1 (sHLA-G1) isoform was found to be secreted by trophoblast cells at the materno-fetal interface, which suggests that it may act as an immunomodulator during pregnancy. In this paper, we reported that GST-sHLA-G1α chain could bind to its receptor ILT-2 on NK92 cells and then the latter recruited Src homology 2 domaincontaining tyrosine phosphatase-1 (SHP-1), which consequently dephosphorylated some important protein tyrosine kinases and blocked the activation of downstream molecules such as ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 25 publications
4
24
0
Order By: Relevance
“…In addition, soluble HLA-G either alone or produced by tumor cells is able to impair NK cell cytolytic activity [55][56][57][58]. Consistent with these findings, we found that M8 tumor cells expressing soluble HLA-G5 isoform were able to inhibit the cytolytic activity of Vc9Vd2 T cells as effectively as M8-HLA-G1 tumor cells (data not shown).…”
Section: Discussionsupporting
confidence: 80%
“…In addition, soluble HLA-G either alone or produced by tumor cells is able to impair NK cell cytolytic activity [55][56][57][58]. Consistent with these findings, we found that M8 tumor cells expressing soluble HLA-G5 isoform were able to inhibit the cytolytic activity of Vc9Vd2 T cells as effectively as M8-HLA-G1 tumor cells (data not shown).…”
Section: Discussionsupporting
confidence: 80%
“…Expression of HLA-G Is Down-Regulated by Targeting siRNA After 48 hours of infection by the recombinant adenovirus containing HLA-G siRNA, HLA-G mRNAs and proteins were isolated from [1] untransfected cells, [2] scrambled siRNA transfected cells, and [3] HLA-G siRNA transfected cells, and were analyzed by RT-PCR and Western blot. The forward and reverse primers used for RT-PCR analysis were specific to exons 5 and 6, respectively, spanning the HLA-G targeting sequences (labeled as P1 and P2 in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1B). Possible explanations for the variance between HLA-G mRNA and protein expression (76.2% vs. 51.57%) in the siRNA-treated cells include [1] that the mRNAs and proteins of different isoforms may be of different abundance, [2] that the antibody used in the present study might not have an equal ability to recognize each isoform, and [3] that steady-state levels of mRNA are not always a good forecaster of steady-state levels of the corresponding protein.…”
Section: Discussion Functional Down-regulation Of Hla-g Isoforms In Tmentioning
confidence: 99%
See 2 more Smart Citations